2023
DOI: 10.1108/ijchm-11-2022-1498
|View full text |Cite
|
Sign up to set email alerts
|

How CEO responsible leadership shapes corporate social responsibility and organization performance: the roles of organizational climates and CEO founder status

Abstract: Purpose This paper aims to investigate how chief executive officer (CEO) responsible leadership impacts corporate social responsibility (CSR) and organization performance by considering diverse organizational climates (including ethical, service and initiative climates) as mediators and CEO founder status as a moderator. Design/methodology/approach This study analyzed survey data from 212 service organizations in China with structural equation modeling. Findings The results clearly established that CEO res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Jang et al [13] gathered data from 250 restaurant managers in the United States. Wang et al [14] used the data from employees both from hotels and restaurants. A quantitative approach utilizing surveys was the primary method (n = 29) employed for data collection in studies investigating sustainability-relevant leadership in the hospitality sector.…”
Section: Context and Methods Employed In The Review Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Jang et al [13] gathered data from 250 restaurant managers in the United States. Wang et al [14] used the data from employees both from hotels and restaurants. A quantitative approach utilizing surveys was the primary method (n = 29) employed for data collection in studies investigating sustainability-relevant leadership in the hospitality sector.…”
Section: Context and Methods Employed In The Review Articlesmentioning
confidence: 99%
“…Jang et al [13] modified the original scale of Voegtlin [34] to fit the specific focus of their study on environmental sustainability. An exception is Wang et al's [14] study, which employed a measurement consisting of 18 items adapted from Agarwal and Bhal [63]. Their research, which included 212 top management team members from various service organizations such as hotels and restaurants, clearly demonstrated the significant impact of CEO-responsible leadership on enhancing both Corporate Social Responsibility (CSR) initiatives and organizational performance through the cultivation of positive organizational climates.…”
Section: How Each Leadership Hypothesized and Measuredmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation between responsible leadership and organisational performance has also been studied in the earlier articles. (Wang et al, 2023) reported that the service, initiative, and ethical climate developed by the CEO's responsible leadership enhances organisational performance. (Huo et al, 2023) reported the existence of a signi cant and positive association between responsible leadership and sustainable performance.…”
Section: Responsible Leadershipmentioning
confidence: 99%
“…The novelty of this study lies in its specific focus on service-oriented companies and comprehensive approach to analyzing various leadership styles and their impact on organizational performance (Kim & Cruz, 2022;Wang et al, 2024;Yan et al, 2020). In addition, this study will also explore mediating factors that might influence the relationship between leadership style and organizational performance, providing deeper insights than previous research.…”
Section: Introductionmentioning
confidence: 99%